A Nonlinear Deterministic Mode Decomposition Strategy for High‐Dimensional Monte Carlo Simulations. Issue 1 (October 2016) - Bamer, Franz; Markert, Bernd
Abstract: We present a new reduced Monte Carlo simulation strategy for nonlinear high‐order systems based on an extension of the proper orthogonal decomposition for transient excited structures. This novel approach enables the evaluation of the response statistics in a fractional amount of time compared to the full Monte Carlo simulation procedure. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)